The habitat of Australia's aboriginal languages : past, present and future - Leitner, Gerhard; Malcolm, Ian G. (Trends in linguistics. Studies and monographs, 2007)
The languages of Aboriginal Australians have attracted a considerable amount of interest among scholars from such diverse fields as linguistics, political studies, archaeology or social history. As a result, there is a large number of studies on a variety.